General and Eating Disorder Specific Flexibility: Development and Validation of the Eating Disorder Flexibility Index (EDFLIX) Questionnaire - Dahlgren, Camilla Lindvall; Hage, Trine Wiig; Wonderlich, Joseph Arthur; Stedal, Kristin (Frontiers in Psychology, 2019)
Findings from studies investigating cognitive flexibility in eating disorders (EDs) are inconsistent, and although neuropsychological tests are commonly used to measure these skills, they may not be particularly effective in predicting everyday functioning. Also, extant studies have largely focused on flexibility in anorexia nervosa (AN), with assessments targeting general rather than specific flexibility, and cognitive, rather than behavioral flexibility. Knowledge regarding ED specific flexibility and flexibility in bulimia nervosa (BN) and binge eating disorder (BED) is still scarce. The aim of this study was to develop and validate a novel measure assessing general and ED specific flexibility in a diagnostically diverse sample, and in healthy controls (HCs). A sample of 207 adult individuals with EDs (55% AN, 29% BN, 16% BED) and 288 HCs responded to an online, 51-item, pilot questionnaire on ED specific and general flexibility. In addition, participants completed the shift subscale from the Behavior Rating Inventory of Executive Function Adult version (BRIEF-A), and the Eating Disorder Diagnostic Scale (EDDS). A principal component analysis (PCA) in the clinical sample yielded a 36-item, three-factor solution capturing general flexibility, flexibility related to food and exercise, and flexibility concerning body shape and weight. Results showed that the measure had good to excellent internal consistency, and good convergent validity. A confirmatory factor analysis (CFA) using data from HCs revealed good fit indexes, supporting the original factor solution. A receiver operating characteristics analysis (ROC) demonstrated excellent accuracy in distinguishing scores from those with and without EDs. A cutoff score of 136 yielded the most balanced sensitivity and specificity. Significant differences in general and ED specific flexibility were found between individuals with and without EDs. Overall, HCs achieved the highest flexibility scores, followed by those with BED, BN, and AN. In sum this novel measure, the Eating Disorder Flexibility Index (EDFLIX) questionnaire, was found to be reliable and valid in the assessment of cognitive and behavioral flexibility, with results offering support for the conceptual distinction between general and ED related flexibility. The study also provides strong evidence for the discriminant validity of the EDFLIX with results revealing significant differences in flexibility in people with and without EDs. In addition, significant differences in flexibility also emerged when comparing diagnostic groups, indicating the utility of the assessment instrument for classification purposes.